2020
DOI: 10.1111/1759-7714.13776
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary metastasis with coexisting pulmonary mucosa‐associated lymphoid tissue (MALT) lymphoma 20 years after endometrioid adenocarcinoma surgery: A case report

Abstract: Late pulmonary metastasis from endometrioid adenocarcinoma (EA) is rare, and occurrence after >20 years is extremely rare. Here, we report a case of pulmonary metastasis with coexisting pulmonary mucosa‐associated lymphoid tissue (MALT) lymphoma that occurred 20 years after surgery for EA. A 60‐year‐old Japanese woman had previously undergone surgery for primary EA, and 20 years later presented with an abnormality that was detected on chest radiography. Chest computed tomography (CT) revealed two nodules in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Histopathological examinations, immunohistochemistry, molecular markers and gene rearrangement studies after surgery are considered effective methods for the confirmation of pulmonary MALToma. [15] The IFE results in this case seem to serve as a reminder. A study revealed that abnormally proliferative monoclonal Igs in serum were helpful for refining the risk assessment of MALToma patients [16] and presented a better ability to predict progression-free survival than International Prognostic Index scores.…”
Section: Discussionmentioning
confidence: 80%
“…Histopathological examinations, immunohistochemistry, molecular markers and gene rearrangement studies after surgery are considered effective methods for the confirmation of pulmonary MALToma. [15] The IFE results in this case seem to serve as a reminder. A study revealed that abnormally proliferative monoclonal Igs in serum were helpful for refining the risk assessment of MALToma patients [16] and presented a better ability to predict progression-free survival than International Prognostic Index scores.…”
Section: Discussionmentioning
confidence: 80%